Pengaruh Citra Destinasi, Nilai Produk dan Kualitas Layanan Terhadap Kepuasan Wisatawan Di Museum Sonobudoyo Yogyakarta - Putri Pebriani; Nining Yuniati; Tonny Hendratono (CV. Ulil Albab Corp, 2023)
Yogyakarta is known as a city with history and culture that is strongly connected with Javanese ancestral values, there are more than 10 (ten) museums in Yogyakarta. The Sonobudoyo Museum is one of the historical tourist destinations in Yogyakarta which has experienced a very productive decline in tourist visits from the 2017-2021 period. The purpose of this study was conducted to determine the effect of destination image, product value, and service quality on tourist satisfaction at the Yogyakarta Sonobudoyo Museum. The sampling technique used purposive sampling with a total of 256 respondents, the data collection instrument used a questionnaire with a Likert scale. Analysis was performed using multiple linear regression, as well as significant tests (t test and F test). The conclusion from this study is that there is an influence of destination image, product value, and service quality on tourist satisfaction at the Sonobudoyo Museum. The correlation coefficient shows that there is a quant relationship between variable X and variable Y.